Amorphous Nanocages of Cu‐Ni‐Fe Hydr(oxy)oxide Prepared by Photocorrosion For Highly Efficient Oxygen Evolution. (25th February 2019) - Cai, Zhi; Li, Lidong; Zhang, Youwei; Yang, Zhao; Yang, Jie; Guo, Yingjie; Guo, Lin
Abstract: Electrochemical water splitting requires efficient, low‐cost water oxidation catalysts to accelerate the sluggish kinetics of the water oxidation reaction. A rapid photocorrosion method is now used to synthesize the homogeneous amorphous nanocages of Cu‐Ni‐Fe hydr(oxy)oxide as a highly efficient electrocatalyst for the oxygen evolution reaction (OER). The as‐fabricated product exhibits a low overpotential of 224 mV on a glassy carbon electrode at 10 mA cm −2 (even lower down to 181 mV when supported on Ni foam) with a Tafel slope of 44 mV dec −1 for OER in an alkaline solution. The obtained catalyst shows an extraordinarily large mass activity of 1464.5 A g −1 at overpotential of 300 mV, which is the highest mass activity for OER. This synthetic strategy may open a brand new pathway to prepare copper‐based ternary amorphous nanocages for greatly enhanced oxygen evolution. Abstract : Rost ansetzen : Eine Methode zur raschen Photokorrosion wurde verwendet, um homogene amorphe Nanokäfige von Cu‐Ni‐Fe‐Hydr(oxy)oxid zu synthetisieren. Diese Nanokäfige sind bemerkenswert effiziente Elektrokatalysatoren für die Sauerstoffentwicklungsreaktion (OER).